Kemampuan Pemecahan Masalah Siswa pada Soal Hots Pola Bilangan di SMP Negeri 1 Teriak - Fransiskus Hendra Gunawan; Hartono Hartono; Abdillah Abdillah (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2024)
Abstract: This research was conducted with the aim of describing students' problem solving abilities on number pattern HOTS questions. The method used in this research is a qualitative research method. The subjects in this research were 6 out of 21 students in class VIII D at SMP Negeri 1 Teriak, each of whom had high, medium and low problem solving abilities. The indicators of problem solving ability according to Polya are: 1) Understanding the problem, 2) Making a resolution plan, 3) Carrying out a resolution plan, 4) Reviewing the resolution plan. The results of this research show that there are 5 students with high level problem solving abilities, 13 students with medium level problem solving abilities and 3 students with low level problem solving abilities. Keywords: Problem Solving, HOTS, Number Patterns